Characteristics and Geochemistry of Organic Lahat Formations as Geological Heritage and Hydrocarbon Potential in Bukit Dua Belas National Park Area, Sarolangun, Jambi. - Alfayed, Muhammad Rus Dody (Teknik Geologi, Fakultas Teknik, Universitas Sriwijaya, 2024)
The study research area is located in the Jambi Sub-Basin which is one part of the South Sumatra basin. Administratively, the research focus area of Sarolangun Regency is in Bukit Suban village. This research includes the study of characteristics and potential hydrocarbon in the Lahat Formation. Research methods are carried out geological surveys and laboratory analysis in the form of petrography, and organic geochemical analysis. Based on data obtained in the study area, the rock characteristics of the Lahat Formation have facies based on (Miall, 1985) having three facies Gmg consisting of polemical breccia lithology, Fsm facies consisting of silt lithology and Fm facies consisting of shale lithology. Based on organic geochemical analysis, the Lahat Formation has a material strength value of sufficient (0.61-1.78), and has a kerogen II type value with a high HI value, and the maturity value is still immature based on Tmax values below <435 and Ro values below <0.6. So based on these data, the Lahat Formation was deposited in an alluvial-lacustrine fan environment, and can be a parent rock that has the potential to produce hydrocarbons with a fairly good category with immature surface sample conditions. Then it can be used as earth research and become a place of geological heritage in the research area.